Resistance risk assessment of Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) to Cry1F protein from Bacillus thuringiensis Berliner in Brazil - Farias, Juliano Ricardo (2014)
The event TC1507 maize with cry1F gene from the bacterium Bacillus thuringiensis Berliner (Bt) was approved for commercial release in Brazil in 2008. The evolution of pest resistance to Bt plants has been a great concern to preserve the lifetime of this technology. Therefore, in this study we assess the risk of evolution of resistance to Cry1F protein in Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) populations from major maize-growing regions in Brazil. The baseline susceptibility to Cry1F was detemined with diet overlay bioassay for susceptible reference population and four field populations of S. frugiperda. Then, we monitored 43 populations of S. frugiperda sampled in nine different States of Brazil during 2010/2011, 2011/2012 and 2012/2013 crop seasons. Only 4-fold variation in susceptibility to Cry1F was detected among S. frugiperda from field populations in the baseline susceptibility study. Diagnostic concentration of 2,000 ng cm-2 was defined for monitoring the susceptibility to Cry1F in S. frugiperda populations. Survival at 2,000 ng cm-2 of Cry1F protein increased significantly throughout crop seasons in populations from São Paulo, Santa Catarina, Rio Grande do Sul, Bahia, Mato Grosso, Goiás, Mato Grosso do Sul, and Paraná, but not in Minas Gerais. We also sampled a population of S. frugiperda in TC1507 field failures in Bahia in October, 2011. This population was selected in laboratory with Cry1F protein up to 20,000 ng cm-2 and the resistance ratio of the selected resistant population (BA25R) was > 5,000-fold. This resistant population was able to survive in Cry1F maize from neonate till pupa and produce normal adult. The inheritance of S. frugiperda resistance to Cry1F protein was autosomal. To test the functional dominance, neonate larvae obtained from the cross of resistant and susceptible populations were tested in leaf bioassay, and around 8% of heterozygotes were able to survive and complete the larval development and produce normal adults on TC1507 leaves while susceptible larvae could not survive for up to five days after infestation. Dominance was estimated to be 0.15 ± 0.09, suggesting that resistance to Cry1F in TC1507 maize was incompletely recessive. We also conducted resistance selection studies in other seven S. frugiperda populations from six different Brazilian states to test whether the resistance alleles were at same locus or not. The F1 larvae obtained from the cross between resistant population (BA25R) and each of the seven selected resistant populations were able to survive at 2,000 ng cm-2 of Cry1F protein in diet bioassay, and therefore they shared the same locus of resistance to Cry1F protein. We estimated the frequency of resistance allele to Cry1F protein in populations of S. frugiperda of main crop season 2011/2012 from five states. We stablished 517 isofemale lines using F2 screen method. The total frequency of Cry1F resistance allele in Brazil was 0.088 with 95% confidence interval between 0.077 and 0.100. Based on results obtained in this study, the risk of resistance evolution to Cry1F protein by S. frugiperda is high in Brazil.